Quantitative assessment of remotely sensed global surface models using various land classes produced from Landsat data in Istanbul - Yastikli, Naci; Sefercik, Umut G.; Esirtgen, Fatih (SPRINGER, 2014)
Digital elevation model (DEM) is the most popular product for three-dimensional (3D) digital representation of bare Earth surface and can be produced by many techniques with different characteristics and ground sampling distances (GSD). Space-borne optical and synthetic aperture radar (SAR) imaging are two of the most preferred and modern techniques for DEM generation. Using them, global DEMs that cover almost entire Earth are produced with low cost and time saving processing. In this study, we aimed to assess the Satellite pour l'observation de la Terre-5 (SPOT-5), High Resolution Stereoscopic (HRS), the Advanced Space-borne Thermal Emission and Reflection Radiometer (ASTER), and the Shuttle Radar Topography Mission (SRTM) C-band global DEMs, produced with space-borne optical and SAR imaging. For the assessment, a reference DEM derived from 1:1000 scaled digital photogrammetric maps was used. The study is performed in 100 km(2) study area in Istanbul including various land classes such as open land, forest, built-up land, scrub and rough terrain obtained from Landsat data. The analyses were realized considering three vertical accuracy types as fundamental, supplemental, and consolidated, defined by national digital elevation program (NDEP) of USA. The results showed that, vertical accuracy of SRTM C-band DEM is better than optical models in all three accuracy types despite having the largest grid spacing. The result of SPOT-5 HRS DEM is very close by SRTM and superior in comparison with ASTER models.
Keywords: digital elevation model (DEM); quantitative assessment; Satellite pour l'observation de la Terre (SPOT); Advanced Space-borne Thermal Emission and Reflection Radiometer (ASTER); Shuttle Radar Topography Mission (SRTM); DIGITAL ELEVATION MODELS; ACCURACY ASSESSMENT; DEM GENERATION; STEREO IMAGES; LIDAR DATA; CATCHMENT; Environmental Sciences & Ecology